Removal of Mercury, Lead and Copper from Aqueous Solution by Activated Carbon of Palm Oil Empty Fruit Bunch - Wahi, Rafeah; Ngaini, Zainab; Usun Jok, Veronica (IDOSI Publications, 2009)
The ability of activated carbon prepared from palm oil empty fruit bunches (EFB) to remove mercury (Hg(II)), lead (Pb(II)) and copper (Cu(II)) from aqueous solutions was investigated. The EFB activated carbon was produced by using chemical and physical activation processes. The adsorption capacity was determined as a function of adsorbate initial concentration and adsorbent dosages. Adsorption isotherms of the studied metals on adsorbent were determined and compared with the Langmuir and Fruendlich isotherm models. The EFB activated carbon showed excellent efficiency in removing Pb(II) and Hg(II) with percentage of removal up to 100% even at low adsorbent dosage. In contrast, only 25% removal of Cu(II) by the EFB activated carbon was observed. The study also showed that the adsorption of Hg(II), Pb(II) and Cu(II) by EFB activated carbon is dependent on the dosage of adsorbent and the initial metals concentration. The use of EFB as activated carbon is not only effective for Hg(II) and Pb(II) removal from wastewater but also helps in solving the problem of over-abundance of EFB as agricultural waste product.